Upaya Pendidik Dalam Membentuk Sikap Moderasi Beragama Terhadap Santri Dayah Darul Hikmah Aceh Barat - Hasan Nuddin; Ammar Zainuddin; Ari Kartiko (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
This research examines educators' efforts to form an attitude of religious moderation towards Dayah Darul Hikmah West Aceh students. Using a descriptive qualitative approach with a case study type of research, data was collected through observation, interviews and documentation. The research results show that Dayah Darul Hikmah West Aceh has systematically improved attitudes toward religious moderation among its students. Efforts begin with careful planning based on the principles of religious moderation from the Indonesian Ministry of Religion, such as tas?muh, tawassuth, taw?zun, itid?l, mus?wah, and sy?ra. Furthermore, educators socialize and apply the values ??of religious moderation in learning in and outside the classroom by emphasizing tolerance, mutual respect and respect for differences. The practice of religious moderation can be seen from an attitude of mutual respect, respect and affection regardless of differences among students. They also maintain good relations with followers of other religions. This practice aligns with multicultural education, peace, character, inclusiveness, and rahmatan lil'alamin. However, there are challenges, such as misunderstanding regarding religious moderation among educators. This research concludes the importance of socialization, in-depth understanding, evaluation and continuous improvement in efforts to increase attitudes towards religious moderation.